Pengaruh Motivasi Kerja, Pengembangan Karir Dan Kompetensi (Hard Skill) Terhadap Kinerja Karyawan (Studi Kasus pada PT. Polowijo Gosari Kabupaten Gresik) - Khuluq, Moh. Nur Khumaini; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to determine the influence of work motivation, career development and competency (hard skills) on employee performance at PT. Polowijo Gosari, Gresik Regency. The location of this research was conducted on employees at PT. Polowijo Gosari, Gresik Regency. This research is quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to employees at PT. Polowijo Gosari, Gresik Regency, was selected using purposive sampling. Determining the sample size used the Slovin formula and the results obtained were 157 respondents. Data were analyzed using multiple linear regression tests and determination tests. Based on the results of data analysis, the F test results show that work motivation, career development and competency (hard skills) simultaneously have a significant and positive effect on the performance of PT employees. Polowijo Gosari, Gresik Regency. Furthermore, the t test results show that work motivation, career development and competency (hard skills) partially have a significant and positive effect on the performance of PT employees. Polowijo Gosari, Gresik Regency. The results of the determination test show that the percentage is 60.5%, where employee performance can be influenced by work motivation, career development and competency (hard skills). Companies should pay more attention to employees' attitudes and behavior at work, one of which is by providing open information about the career development and competencies of each individual employee so that employees will be able to maximize their performance within the company. Keywords: Employee Performance, Work Motivation, Career Development, Competence (hard skills).